Hambatan Utama Implementasi Merdeka Belajar pada Perguruan Tinggi Swasta - Bisri, Abdul Mukti; Muid, Abdul; Khamim, Nur (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Independent Learning Independent Campus (MBKM) was launched by the Ministry of Education, Culture, and Research and Technology to support the readiness of students to face challenges in the world of work by applying active learning. Documentary institutions in universities, namely libraries, archives, and museums, should become strategic partners in supporting the MBKM program because the documentary institution has all the necessary conditions, facilities, and infrastructure to succeed MBKM program. This study aimed to determine the problem of program implementation faced by institutions in the private universities in East Java and what obstacles they encountered. This study used the qualitative method and in-depth interviews for data collection and a literature study. The researcher concludes that the biggest challenges facing institutions are lack of information,  regulation and the readiness of resources. Due to this, changes to regulations and educational curricula and the introduction of new documentation of pure science are priorities in improving professional education.